Periprocedural Peritonitis Prophylaxis: A Summary of the Microbiology and the Role of Systemic Antimicrobials - Leon Hsueh; Susie L. Hu; Ankur D. Shah (Karger Publishers, 2021)
Background: Peritonitis is a leading complication of peritoneal dialysis (PD). One strategy that the International Society for Peritoneal Dialysis (ISPD) has used to help mitigate the morbidity and mortality associated with peritonitis is through prevention, including antibiotic prophylaxis utilization in high-risk situations. The aim of this study is to summarize our current understanding of postprocedural peritonitis and discuss the existing data behind periprocedural antibiotic prophylaxis, focusing primarily on PD catheter insertion, dental procedures, colonoscopies, upper endoscopies with gastrostomy, and gynecologic procedures. Summary: The ISPD currently recommends intravenous antibiotics prior to PD catheter insertion, colonoscopies, and invasive gynecologic procedures, though prophylaxis has only demonstrated benefit in a prospective, randomized control setting for PD catheter insertion. However, multiple retrospective studies exist that support the use of antibiotic prophylaxis for the other 2 procedures. No specific antibiotic regimen has been established as most optimal to prevent peritonitis for any of the 3 procedures. Antibiotic coverage should include the Enterobacteriaceae family, as well as Gram-positive organisms commonly found on the skin flora for PD catheter insertion, anaerobes for colonoscopies, and common organisms from the urogenital flora in gynecologic procedures. Additionally, the ISPD currently recommends oral amoxicillin prior to dental procedures. There is currently no ISPD recommendation to provide antibiotic prophylaxis prior to an upper endoscopy with or without gastrostomy, though this is a potential area for research. Key Messages: PD patients are at high risk for developing peritonitis after typical procedures. Antibiotic prophylaxis is a potential strategy that the ISPD utilizes to prevent these infections. However, further research needs to be done to determine the optimal antibiotic regimen.